Analisa Produksi Bio-Etanol Dari Kulit Singkong Dengan Proses Thermal - Sabilah, Laode Muhamad Zakirus; Mangalla, Lukas Kano; Imran, Al Ichlas (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2020)
Cassava skin is a waste of high-carbohydrate cassava that can be treated asa an alternative fuel source. As for the purpose of this study, it is to know how to produce bioethanol  from  cassava  skin  and  how  much  ethanol  is  produced  in  the fermentation  destilation  procwss.  Bioethanol  research  from  the  cassava  skin  is made by means of a fermentation process using a 9 and 12 day fariation with a 20,4 and 60 gram supplement of a mixture (leaven/yeast) of a 20,4 and 60 gram that is cut  off  by  sample  destilting  devices.  Research  shows  that  the  longer  the fermentation from a mixture of refined caskbark and yeasts does not significantly affect the ethanol produced, since ethanol results from each fariation is 10%. Key words: Cassava suede, fermentation, bioethanol, renewable energy